PEMBERDAYAAN MASYARAKAT MELALUI PENGOLAHAN IKAN MENJADI ABON DAN NUGGET IKAN - Sitti Khotijah (Universitas Al-Amien Prenduan, 2023)
The Potency of naturalÂ resources, in this case fishes, is one of the important asset and have goodprospect in empowering the society. So that, fishes as natural resources were required to get special attention both in managing and processing so the high protein in fishes could be safe. The fishes that naturally soon be rotten, need to processed by the innovation and creativity of the society thus the fishes will still have the worth selling. The empowerment program that conducted by all member of P@M Institute Dirosat Islamiyah Al-Amien at Tamberuh Timur village empowered the society by increasing the fishes as their natural resources potency inti Abon Wolez and Nugget Wolez Wolez. The mothed used in this program is ABCD methods, and the result ofÂ this program is processed fishes into Abon Wolez and Nugget Wolez were conducted in many steps as follows: First, Preparation. Field survey, observation, and interview with the villager of Tamberuh Timur.Second, Choosing the superiorÂ assets as priority. Third, Action-socialization. Fourth, Implementation. Are product training and product launching. Fifth, Sharing product and closing the P2M program. The inhibitingfactors found are: thr lack of social organization of community, the lack of facilities and infrastuctures.Akbar, Idham Nourgama, and Dwi Sulistiani. â€œPeran Organisasi Sosial Preman Super Dalam Pemberdayaan Perempuan Di Malang Raya.â€ Jurnal Kesetaraan dan Keadilan Gender 14, no. 1 (2019).Dumasari. Dinamika Pengembangan Masyarakat Partisipatif. Yogyakarta: Universitas Muhammadiyah Purwokerto Press Bekerjasama dengan Pustaka Pelajar Yogyakarta, 2014.Gemaputri, Ariesia A. â€œTingkat Pemanfaatan Sumber Daya Ikan Hasil Tangkapan Di Perairan Jember.â€ Jurnal Perikanan (J.Fish, Sci) XV, no. 1 (2013): 35â€“41.Gendalasari, Gen Gen. â€œPembinaan Organisasi Sosial Kemasyarakatan Mengenai Dampak Pandemi Covid-19 Terhadap Budaya Organisasi Di Kecamatan Tamansai Kabupaten Bogor.â€ JADKES, jurnal Abdimas Dedikasi Kesatuan 1, no. 1 (2020): 21â€“23.Hamid, Hendrawati. Manajemen Pemberdayaan Masyarakat. Makasar: De La Macca, n.d.Juwita, Tita Meirina, and Dadang Hermawan. â€œImplementai Kebijakan Organisasi Kemasyarakatan Di Kabupaten Bandung.â€ JIMIA: Jurnal Iliah Magister Ilmu Administrasi 12, no. 2 (2018).Maulana, Mirza. â€œAsset-Bassed Community Development: Strategi Pengembangan Masyarakat Di Desa Wisata Ledok Sambi Kaliurang.â€ Empowerâ€¯: Jurnal Pengembangan Masyarakat Islam 4, no. 2 (2019).Purbantara, Arif, and Mujianto. KKN Desa Tematik Desa Membangun Pemberdayaaan Masyarakat Desaâ€. Kementrian Desa, Pembangunan Daerah Tertinggal dan Transmigrasi Republik Indonesia, n.d.Riyanti, Chika, and Santoso Tri Raharjo. â€œAsset Based Community Development Dalam Program Corporate Social Responsibility (CSR).â€ Jurnal Kolaborasi Resolusi Konflik 3 (2021): 115â€“126.Zakky, Nurdody, Isdiantoni, and Isnani Yuli Andini. â€œAnalisis Potensi Dan Tingkat Perkembangan Desa Di Kabupaten Sumenep.â€ Jurnal performance Bisnis dan Akuntansi VII, no. 1 (2017): 67.Â